Magallana gigas - Jirapatrasilp, Parin; Cuny, Gilles; Kocsis, László; Sutcharit, Chirasak; Ngamnisai, Nom; Charoentitirat, Thasinee; Kumpitak, Satapat; Suraprasit, Kantapon (Zenodo, 2024)
Magallana cf. gigas (Thunberg, 1793) Figs 12 E, 14 D cf. Ostrea gigas Thunberg, 1793: 140 – 142, pl. 6, figs 1 – 3. Type locality: Japan. Yokoyama 1927: 402. cf. Crassostrea gigas . Tantanasiriwong 1979: 7. Nateewathana et al. 1981: 65. Poutiers 1998 a: 233, with in-text figs. Aungtonya et al. 1999: 375. Robba et al. 2002: 69, 71, pl. 5, fig. 3 a, b. Hylleberg and Kilburn 2003: 162. Beu et al. 2004: 154 – 156, fig. 9 d. Thach 2005: 257. Robba et al. 2007: 84 (appendix). Printrakoon et al. 2008: table 1. Huber 2010: 180, with in-text fig. Sanpanich 2011: table 2. Huber 2015: C 5155. Okutani 2017: 1183, pl. 483, fig. 7. Yang et al. 2017: 176, 178, fig. 685. Surakiatchai et al. 2018: table 6, pl. 3, fig. 6 a, b. Tudu et al. 2018: table 1. cf. Crassostrea cf. gigas . Swennen et al. 2001: 45, 72, text-fig. 62, fig. 62. cf. Crassostrea ( Magallana ) gigas . Lutaenko et al. 2019: 187 – 188, pl. 15, fig. a – f. cf. Magallana gigas . Wells et al. 2021: 60. Referred material. CUF - NKNY - B 13 (130 L + 16 R shells; Figs 12 E, 14 D). Habitat. Attached to rocks from intertidal zones down to 30 m depth, in mud, bays, and sheltered areas that are often brackish with low salinity water (Thach 2005; Huber 2015). Distribution. Cosmopolitan (Huber 2015). Records of fossils from the Miocene to Holocene in Japan, New Zealand, Taiwan, and Thailand (Robba et al. 2002; Beu et al. 2004; Surakiatchai et al. 2018). Record in Thailand. Gulf of Thailand and Andaman Sea (Wells et al. 2021). Taxonomic remarks and comparisons. The cupped oysters in the subfamily Crassostreinae could not be identified at species level based on shell characters or soft tissue alone (Salvi and Mariottini 2021). Therefore, we tentatively identify these specimens of giant cupped oysters as belonging to Magallana gigas , due to large and thick shells and the presence of this species in Thailand (Wells et al. 2021). Order Pectinida Gray, 1854 Superfamily Anomioidea Rafinesque, 1815 Published as part of Jirapatrasilp, Parin, Cuny, Gilles, Kocsis, László, Sutcharit, ...